Alternatives for Connecting Photovoltaic Generators to Power Systems with Three-Port and Partial Power Converters - Donghui Ye; Sergio Martinez (Applied Sciences)
Solar electricity has become one of the most important renewable power sources due to rapid developments in the manufacturing of photovoltaic (PV) cells and power electronic techniques as well as the consciousness of environmental protection. In general, PV panels are connected to DC-DC converters and/or DC-AC inverters to implement the maximum power point tracking algorithm and to fulfill the load requirements. Thus, power conversion efficiency and power density need to be taken into consideration when designing PV systems. Three-port and partial power conversion technologies are proposed to improve the efficiency of a whole PV system and its power density. In this paper, three types of three-port converters (TPCs), including fully isolated, partly isolated, and non-isolated TPCs, are studied with detailed discussions of advantages, disadvantages, and comparisons. In addition, based on partial power conversion technologies, partial power two-port and three-port topologies are analyzed in detail. Their efficiency and power density can be further improved by the combination of three-port and partial power conversion technologies. Moreover, comparisons among seven different types of distributed PV systems are presented with their advantages and disadvantages. Compared to distributed PV systems without energy storage, distributed PV systems with hybridization of energy storage and with partial power regulation can use solar energy in a more efficient way.